Gram-negative bacteria facilitate tumor outgrowth and metastasis by promoting lipid synthesis in lung cancer patients - Ye, Maosong; Gu, Xia; Han, Yang; Jin, Meiling; Ren, Tao (Journal of Thoracic Disease, 2016)
Background: Lung cancer is the leading cause of cancer-related death worldwide. Patients with lung cancer are very frequently present with pulmonary infections, in particular with Gram-negative bacteria. Herein, we investigated the effect of the co-presence of Gram-negative bacteria on outgrowth and metastasis of lung cancer cells in clinical patients. Methods: Lung cancer cells were isolated from clinical surgical tissues. Heat-inactivated E. coli was used as Gram-negative bacteria. Tumor outgrowth and invasion in vitro was analyzed with MTT assay and Biocoat Matrigel Invasion Chamber. Tumor growth and metastasis in vivo was evaluated in BALB/c nude mice. Lipid synthesis was evidenced by expressions of FASN and ACC1, as well as BODIPY Fluorophores staining. Block lipid synthesis was performed with C75 as a FAS inhibitor and transfection with ACC1 siRNA. Knockdown of TLR4 and TLR9 signaling was achieved by transfection with specific shRNAs and administration of specific antagonists. Results: Gram-negative bacteria significantly promoted lung cancer development including growth and metastasis in dose dependent manner. Mechanistically, Gram-negative bacteria activate TLR4 and TLR9 signaling and enhance lipid synthesis in human lung cancer cells. Knockdown of TLR4 and/or TLR9 was able to block Gram-negative bacteria mediated lipid synthesis and lung cancer development. Interference with lipid synthesis efficiently abrogated Gram-negative-bacteria-induced lung cancer development. In lung cancer patients, higher expressions of innate immune receptors, TLR4 and TLR9, were observed in those with Gram-negative infections and associated with the aberrant lipid synthesis that was observed in vitro. Conclusions: Pulmonary infections with Gram-negative bacteria lead to aberrant lipid synthesis through TLR4 and TLR9 signaling in lung cancer patients and result in rapid proliferation and metastasis of lung cancer cells. These findings reveal a new mechanism for pulmonary infection-trigged caner development and provide clues for exploring therapeutics for lung cancer patients.